Failure Diagnosis for Demagnetization in Interior Permanent Magnet Synchronous Motors - Takeo Ishikawa; Naoto Igarashi; Nobuyuki Kurita (International Journal of Rotating Machinery)
Since a high degree of reliability is necessary for permanent magnet synchronous motors, the detection of a precursor for the demagnetization of permanent magnets is very important. This paper investigates the diagnosis of very slight PM demagnetization. The permanent magnet volume is altered so as to mimic the effect of demagnetization. This paper investigates the influence of demagnetization by using several methods: the 3D finite element analysis (FEA) of the motor, the measurement of high-frequency impedance, and the measurement and FEA of the stator voltage and current under vector control. We have obtained the following results. The back-EMF is proportional to permanent magnet volume, and there is no difference in the demagnetization in the radial direction and in the axial direction. Even harmonics and subharmonics of flux density at the teeth tip could be useful for diagnosis if a search coil is installed there. The relatively low frequency resistance at the d-axis position is useful for diagnosis. Under vector control, the stator voltage is useful except in an intermediate torque range, and the intermediate torque is expressed by a simple equation.